Expression features of CD16 and NKG2D receptors by NK cells, NKT cells and T lymphocytes of peripheral blood associated with female infertility - V. A. Mikhailova; A. A. Davydova; V. A. Zagaynova; O. B. Marko; E. R. Mkrtchyan; A. S. Zhguleva; O. A. Bakulina; S. A. Selkov; O. N. Bespalova; D. I. Sokolov (Медицинская иммунология)
The increasing incidence of infertility determines relevance of studying various cellular factors, including immune cells, in pathogenesis of this disorder. In cases of infertility, some changes are described in NK cell activation in decidual and peripheral blood cells, as well as in representation of NKT cells and T lymphocytes in uterus at miscarriage (MC). NK cells and NKT cells are characterized by expression of activating receptor NKG2D and a receptor for immunoglobulin G Fc-region CD16. Distinct populations of T lymphocytes express NKG2D. The aim of the present study was to analyze the expression of CD16 and NKG2D by NK cells, NKT cells and NKG2D receptor by peripheral blood T lymphocytes. We examined 60 women with infertility. The control group consisted of healthy non-pregnant fertile women (n = 17). Mononuclear cells were obtained from peripheral blood and treated with monoclonal antibodies to CD45, CD14, CD3, CD56, CD16, NKG2D. The intensity of NKG2D receptor expression on peripheral blood NKT cells in patients with primary infertility proved to be lower than in healthy non-pregnant fertile women. This difference may be caused by the absence of an embryo implantation in previous history of primary infertility and, accordingly, lacking influence of cytokines and cellular microenvironment specific for first trimester of pregnancy. In patients with secondary infertility and miscarriage (MC), the relative numbers of CD16+NK cells and CD16+NKG2D-NK cells in peripheral blood were reduced when compared to the women with secondary infertility without history of MC. Relative numbers of CD16+NK cells and CD16+NKG2D-NK cells in peripheral blood were also reduced in patients with secondary infertility and MC compared to patients with primary infertility and to healthy non-pregnant fertile women. CD16 expression intensity of NK cells was shown to be reduced in subgroup of women with secondary infertility and a history of MC compared to control group and to women with secondary infertility without a history of MC. No differences in NKG2D expression by T lymphocytes associated with infertility were found. Reduced CD16 expression by NK cells of women with secondary infertility and MC may reflect the impaired functional differentiation of NK cells associated with this condition.